Polymorphism, Heteroplasmy, Mitochondrial Fusion and Diabetes. Issue 5 (October 2003) - Sato, Aya; Endo, Hitoshi; Umetsu, Kazuo; Sone, Hideyuki; Yanagisawa, Yoshiko; Saigusa, Azusa; Aita, Sayuri; Kagawa, Yasuo
Abstract : Mitochondrial DNA (mtDNA) is highly susceptible to mutations that result in polymorphisms and diseases including diabetes. We analyzed heteroplasmy, polymorphisms related to diabetes, and complementation by fusogenic proteins. Cytoplast fusion and microinjection allow, defects in mutated mtDNA inside a heteroplasmic cell to be complemented by fusing two mitochondria via human fusogenic proteins. We characterized three hfzos as well as two OPA1s that prevent apoptosis. Two coiled coil domains and GTPase domains in these fusogenic proteins regulate membrane fusion. The hfzo genes were expressed mainly in the brain and in muscle that are postmitotic, but not in the pancreas. Under the in.uence of polymorphisms of mtDNA and nDNA, the vicious circle of reactive oxygen species and mutations in cell can be alleviated by mitochondrial fusion.